Epidemiological profile of cancer patients from an area with high pesticide use - Pluth, Thaís; Zanini, Lucas; Battisti, Iara; Kaszubowski, Erikson (Saúde em Debate, 2022)
Pesticide consumption has increased considerably in the last years. Although pesticides have helped to increase the crops’ productivity, they have been associated with the incidence of cancers. The objective of this study was to describe the epidemiological profile of cancer patients living in an area with high use of pesticide. A retrospective cohort design was used to describe cancer cases. Patients were included whenever (i) diagnosed with any type of cancer between 2005 and 2016; (ii) living, at the time of diagnosis, in one of the 69 Brazilian cities studied; and (iii) aged 12 years old or over. A multilevel regression model was used to model the cancer morbidity coefficient. A total of 10,640 cancer patients were studied. Cancer morbidity coefficients increased with age and were significantly higher among people residing in rural areas than among those living in urban areas (p-value<0.0001). In both urban and rural areas, males showed significantly higher cancer morbidity coefficients than females. This study suggests that higher cancer incidence is related to factors of rural life, which can include pesticide exposure since the studied area is known for its agriculture based economy and high pesticide use.